2017
DOI: 10.1002/pola.28692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multiblock ethylene/long‐chain α‐olefin copolymer via chain walking polymerization using thermostable α‐diimine nickel catalyst

Abstract: INTRODUCTIONIn recent years, there has been an explosion of research committed to the olefin block copolymers with diverse microstructures. Melting temperatures, glass transition temperatures, and mechanical properties of materials can be altered, when alkyl branches were introduced into carbon hydrogen backbone. 1 This was attributed to the reduction of main chain crystallinity by the alkyl branches. Brookhart et al. demonstrated that some late transition metal catalysts bearing bulky a-diimine ligand exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the late 1990s, Brookhart and co-workers reported cationic late-transition metal α-diimine complexes [ 1 (Figure )] for the polymerization of olefins. Since this initial disclosure, the α-diimine ligand framework has permitted tuning of the polyolefin microstructure, functionality, topology, and properties. The versatility of this reaction platform is facilitated by the unique “chain-walking” behavior of these catalysts, which may be modulated by the choice of metal and the substituents on the α-diimine nitrogens and backbone . Chain-walking comprises consecutive β - hydride elimination and re-insertion of the metal center with opposite regiochemistry along the polymer backbone (see Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s, Brookhart and co-workers reported cationic late-transition metal α-diimine complexes [ 1 (Figure )] for the polymerization of olefins. Since this initial disclosure, the α-diimine ligand framework has permitted tuning of the polyolefin microstructure, functionality, topology, and properties. The versatility of this reaction platform is facilitated by the unique “chain-walking” behavior of these catalysts, which may be modulated by the choice of metal and the substituents on the α-diimine nitrogens and backbone . Chain-walking comprises consecutive β - hydride elimination and re-insertion of the metal center with opposite regiochemistry along the polymer backbone (see Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the novel C­(sp 3 )–C­(sp 3 ) coupling reaction could be utilized for the construction of valuable ABA-type polyolefin triblock copolymers, which are expected to exhibit useful thermoplastic elastomer properties (Scheme ). Typically, the number-average molecular weight ( M n ) attainable in CCTP is limited (∼60 kDa). This work provides a method to prepare high molecular weight POs in CCTP and overcoming this limitation.…”
Section: Introductionmentioning
confidence: 99%